Advertisement Remove all ads

Solve: 3(2x + 1) - 2x+2 + 5 = 0. - Mathematics

Sum

Solve : 3(2x + 1) - 2x+2 + 5 = 0.

Advertisement Remove all ads

Solution

3(2x + 1) - 2x+2 + 5 = 0.
⇒ 3 x 2x + 3 - 2x x 22 + 5 = 0
⇒ 2x ( 3 - 22 ) + 8 = 0
⇒ 2x ( 3 - 4 ) = - 8
⇒ 2x x ( - 1 ) = - 8
⇒ 2x = 8
⇒ 2x = 23
⇒ x = 3

Concept: Simplification of Expressions
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (C) | Q 10 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×